Importance Factor Analysis of Quality Assurance for Contractor Competitiveness - Ashari Putri, Mega Dewi; Devia, Yatnanta Padma; Anwar, M. Ruslin (Rekayasa Sipil, 2024)
Population growth led to massive construction development, with increasing demand every year. One of those demands is housing construction. The high demand for this house has led to the emergence of new contractors on a local scale, with products and services of unstable quality. Hence, the contractors need to be more competitive in the industry. This research aims to identify and analyze the important factors influencing quality assurance (QA) and the competitiveness of local contractors in housing construction projects. The analysis is grounded in three primary frameworks: ISO 9001:2015 (Quality Management Systems), PMBOK 6th Edition (Project Management Body of Knowledge), and Ministry of Public Works and Public Housing Regulation No. 4 of 2009. The research design used statistical analysis, Relative Importance Index (RII), and Analytical Hierarchy Process (AHP) to identify key factors. Research findings indicate that leadership commitment, project resources, and quality documentation are the three most critical factors. Regardless of the identified critical factors, all factors contribute to a significant influence on successful performance. The proposed strategic approach involves sequentially improving the "quality of work output," followed by "customer retention" and "project cycle efficiency." These findings can serve as a guideline for contractors in making decisions to enhance their competitiveness.